Constraints Analysis of KISSAN KERALA User Farmers in Utilizing Multi Modal-Delivery Services (Indian Journal of Extension Education, 2017)
Karshaka Information System Services and Networking (KISSAN Kerala) is a multimodal agri-advisory service started by Kerala government. The study was conducted in two districts of Kerala: Alappuzha and Thrissur. A total of 240 user farmers were selected for the study. KISSAN Kerala has mainly five mode of agri-advisory service. The study focussed to bring out the constraints and suggestions faced by the user-farmers in accessing the services. Data was collected using interview schedule. The user-farmers were asked to express their constraints and suggestions. The responses were converted into frequency and ranked. Majority opined about the difficulty in accessing the online agri-advsiory services of KISSAN Kerala.